International Sharing of Polar Information Resources: proceedings of the 14th Polar Libraries Colloquy, May 3-7, 1992 Byrd Polar Research Center, The Ohio State University, Columbus, Ohio, USA. - Lay, Lynn B, editor; Tipton Everett, Lynn, editor (1992)
Papers presented at the 14th Polar Libraries Colloquy, held May 3-7, 1992 at the Byrd Polar Research Center, Columbus, Ohio. Published as BPRC Report no. 4.